Estimating the Prevalence of Mental and Substance Use Disorders: A Systematic Approach to Triangulating Available Data to Inform Health Systems Planning. (February 2022) - Vigo, Daniel; Jones, Wayne; Dove, Naomi; Maidana, Daniel E.; Tallon, Corinne; Small, Will; Samji, Hasina
Objective: To estimate the prevalence of specific mental and substance use disorders (MSUDs), by age and sex, as a first step toward informing needs-based health systems planning by decision-makers. Methods: We developed a conceptual framework and a systematic methodology for combining available data sources to yield prevalence estimates for specific MSUDs. Data sources used included published, peer-reviewed literature from Canada and comparable countries, Canadian population survey data, and health administrative data from British Columbia. Several well-established methodologies including systematic review and meta-analyses of published prevalence estimates, modelling of age- and sex-specific distributions, and the Global Burden of Disease severity distribution model were incorporated in a novel mode of triangulation. Results: Using this novel approach, we obtained prevalence estimates for 10 MSUDs for British Columbia, Canada, as well as prevalence distributions across age groups, by sex. Conclusion: Obtaining reliable assessments of disorder prevalence and severity is a useful first step toward rationally estimating service need and plan health services. We propose a methodology to leverage existing information to obtain robust estimates in a timely manner and with sufficient granularity to, after adjusting for comorbidity and matching with severity-specific service bundles, inform need-based planning efforts for adult (15 years and older) mental health and substance use services.